L'esempio di Silvio Trentin : Scritti 1954-1991 - Norberto Bobbio Pietro Polito; Pina Impagliazzo (Firenze University Press, 2020)
Using unpublished documents, this volume restores the meeting between two masters in a historical and ideal way: Norberto Bobbio and Silvio Trentin. Through the writings which Bobbio dedicated to Trentin between 1954 and 1991, the readers are introduced to Trentin$1 (Bs world. They gradually discover Trentin$1 (Bs exemplary biography, his clear moral personality and his commitment to anti-fascism and the Resistance, as well as the great themes of his work as a jurist and political thinker: the criticism of fascism, federalism and the idea of the 'third way'. As Bobbio observes, the fundamental reason why Trentin represents a still valuable example is that, through his life and thought, he has perfectly embodied the conception of politics as a desire of justice, as opposed to the will to dominate.s
Keywords: Silvio Trentin; third way; federalism; anti-fascism; Norberto Bobbio